Dinâmicas adaptativas de arte ambiental em contexto erosivo - Naidin, Julia (Resistances. Journal of the Philosophy of History.)
CasaDuna - Centro de arte, pesquisa e memória de Atafonais an art residence based on Atafona beach, in the municipality of São João da Barra, in the north coast of the state of Rio de Janeiro. The region, close to the Paraíba do Sul river delta, suffers for over fifty years an intense process of coastal erosion. We intend to expose reports of an interdisciplinary experience based on an action research methodology, in contemporary art productions that operate with contextual agency. We argue that there is an ethical, aesthetic and political dimension when proposing to work with the environment with regard to the possibility of developing actions that affect imaginary and epistemologies in the relationship with the territory. These are notes on the development of a pedagogical mediation and curatorial work in an artistic residency in an erosive context.